Community economic development in two rural Kansas communities: a thematic analysis - Colle, Kevin Loren (My University, 2025)
Rural communities across Kansas face growing challenges of population decline, limited financial resources, and shifting economic structures. This study examines the factors that shape community economic development (CED) in two rural Kansas towns, Sterling and Nickerson, using the Community Capitals Framework (CCF) as an analytical lens. The CCF identifies seven interrelated forms of capital that collectively influence a community’s development trajectory. Through a qualitative comparative case study approach, nine semi-structured interviews were conducted with local leaders and stakeholders from both communities. Data were coded deductively using the seven capitals and analyzed inductively through thematic analysis. Findings reveal four interrelated themes shaping CED in these communities: (1) the power and limits of social capital, (2) political capital as a gatekeeper to development, (3) identity and attachment to place, and (4) built strengths and constraints. The study concludes that communities with well-coordinated political, social, built, and cultural capitals are more likely to “spiral up” toward sustainable growth, while those with fragmented or exclusionary networks risk “spiraling down.” By applying the CCF to rural Kansas, this study contributes to the understanding of how small towns mobilize their assets amid structural and demographic challenges. The findings offer insights for policymakers, local leaders, and development practitioners seeking to strengthen community resilience and guide equitable economic growth in rural America.
Keywords: Commuinty development; Thematic analysis; Rural development; Community economic development; Community capitals framework